2013
DOI: 10.31018/jans.v5i2.324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wood particle geometry and pre-treatments on the strength and sorption properties of cement-bonded particle boards

Abstract: The effect of particle geometry and pretreatments on the strength and sorption properties of wood particle cement composite boards was investigated. Wood particles (flakes and sawdust) of Gmelina arborea were mixed with cement and water in the production of composite boards. The wood particles were pretreated with hot water, calcium chloride and a combination of both treatments to enhance bonding with cement. The slurry was poured into rectangular moulds for board formation. After demoulding, the boards formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…It was concluded that the modification of fibres results in improved surface properties and reduced hydroxyl groups, thereby enhancing the properties of the composite material. Similarly, the use of cement setting accelerators, which reduces the hydration time of cement has been reported to yield good results [2,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the modification of fibres results in improved surface properties and reduced hydroxyl groups, thereby enhancing the properties of the composite material. Similarly, the use of cement setting accelerators, which reduces the hydration time of cement has been reported to yield good results [2,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, cabe destacar as espécies do gênero Pinus pesquisadas por Lima et al (2011); espécies de Eucalyptus, por Iwakiri e Prata (2008), Castro et al (2015) e Iwakiri et al (2015); além de espécies de madeiras tropicais como Schizolobium amazonicum e Cecropia hololeuca (IWAKIRI et al (2012) e Gmelina arbórea (AMIANDAMHEN;IZEKOR (2013).…”
Section: Introductionunclassified
“…These limitations have been addressed by several techniques, for example, hot water extraction and leaching in cold water have been effective in removing the detrimental components [18,19] and chemical extractions have also shown positive effects [17,20,21]. The use of cement curing accelerators like CaCl 2 , MgCl 2 and CaCO 3 has been helpful in eliminating the need to pre-soak the wood particles [1,22,23]. Other methods that have been used to improve compatibility between wood and cement are fungal treatment of wood [24]; application of blocking layers around wood particles [25]; CO 2 treatment [26,27]; and the addition of pozzolans, such as volcanic ash, fly ash, rice husk ash and condensed silica fume [18,28].…”
Section: Portland Cement Bonded Compositesmentioning
confidence: 99%